The bacteriological prevalence of leptospiral infection in cattle and buffaloes in West Malaysia - Bahaman, A. R.; Ibrahim, A. L.; Stallman, N. D.; Tinniswood, R. D. (1988)
A cross-sectional bacteriological survey of cattle in West Malaysia revealed 14·4% (32/222) had leptospiral infection. Isolates were obtained from all except one herd with prevalence of infection in herds ranging from 0—44·8%. A small number of buffalo urine samples were examined and all of them were found to be negative. A leptospiral isolate obtained from a bovine kidney proved to be n new scrovar of Leplospira interrogans and the name unipertama was assigned to it. Six other leptospiral serovars were isolated, namely canicola, australis, javanica, ballum, pomona and hardjo. All six serovars were isolated for the first time in cattle in Malaysia. Cattle in Malaysia appear to be the maintenance host for serovar hardjo. The presence of the other serovars in cattle was probably duo to contact with the maintenance hosts, pigs for serovar pomona and rodents for the other three serovars. It appears that the epidemiology of leptospiral infection in cattle in Malaysia is similar to that reported overseas. © 1988, Cambridge University Press. All rights reserved.